Mengkaji Ciri-Ciri Jalan Dua Lorong Dua Hala Untuk Keadaan Lalu Lintas Di Malaysia (Skop Kawasan Nibong Tebal) - Suhaimi, Izatil Fadhilah (Universiti Sains Malaysia, 2006)
Two-lanes-two-way highway is a type of road that can carry high volume of traffic. This situation become more serious if the value of headways is very small. The car following behavior is one of the many aspects that are considered to influence road crashes and the road traffic handling capacity. The purpose of this thesis is to determine the level of services for Jalan Bukit Panchor, Jalan Bandar Baharu and Jalan Bukit Panchor Paper Mill using the HCM 2000 method. This method is also used to analyse level of services using the Arahan Teknik Jalan 8/86 (Jalan). The level of service from the two methods are compared. Beside that, linear regression models were developed to get the relationship between distance headway and speed. The data for this two-lane-two-directions road will be determined by the help of ‘Metro Count’ programmed to get the traffic value. The distance headways and associated vehicle speed were separated into several categories by vehicle type and then separated into speed classes according to type of vehicle following i.e., car following car, car following heavy goods vehicle (HGV), HGV following HGV and HGV following car categories. As a result from this project, we know that there is no significant method in estimating level of service for the Arahan Teknik Jalan 8/86 (Jalan) whereas it can be done by using the Highway Capacity Manual 2000. For relationship between distance headway and speed, drivers tend to follow another vehicle closely and platoon appeared to develop rapidly.